(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The differences between a psychologist, a counselor and atherapist might seem minuscule to some people, but there are actually somemajor differences between these professional titles. While all mental healthprofessionals talk to people and help them through various problems in theirlives, the education they get and the way they are trained can differ greatly.There are different academic and licensure standards for each profession anddifferent roles they can fulfill.